FUZZY_FTA - A SIMPLIFIED METHOD FAULT TREE ANALYSIS OF COMPLEX SYSTEMS - Romanenko, Arsenii; Kosolapov, Anatolii (European Science, 2025)
The paper presents an analysis of the most popular mechanisms for ensuring the fault tolerance of complex systems, such as socio-cyber-physical systems (SCPS). The most popular is the method of analyzing fault trees, which are represented in the form of l